Matkovska I. V. Linguo-stylistic peculiarities of black vernacular (on the pattern of Z. Hurston`s novel “Their eyes were watching God” - Matkovska I. V. (Philological Treatises, 2020)
This article is devoted to the study of linguo-stylistic peculiarities of black vernacular. The author demonstrates them on the pattern of Z. Hurston`s novel “Their Eyes were watching God”. The phonetical, lexico-grammatical levels of black vernacular of the novel are analysed in the article to show the specific nature and atmosphere of the socio-cultural life in the south of the USA.